2021
DOI: 10.1111/aman.13556
|View full text |Cite
|
Sign up to set email alerts
|

Risky Appearances, Skillful Performances: Female Islamic Preachers and Professional Style in Malaysia

Abstract: Mass involvement of women in Islamic associations and public religious expressions has led to an unprecedented demand for women Islamic authorities. Yet, paradoxically, the global Islamic revival has also strengthened conservative norms with regard to the exposure of women's bodies and voices. In Malaysia, women Islamic popular preachers navigate, and to some extent obviate, this tension between publicity and modesty by cultivating a professional style. In the context of mass education, mass mediatization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…These phenomena speak to broader themes in the anthropology of Islam, gender, and religious authority, in which ethnographic studies have demonstrated how women take up the mantle of Muslim femininity to maintain their respectability as they claim territory in social and authoritative roles and spaces once the purview of men. Women may extol the virtues of Muslim gender norms while simultaneously claiming new forms of religious authority as women preachers (Kalmbach 2008; Kloos 2021), activists (Deeb 2006), Sufi teachers within a patrilineal lineage (Hill 2018), or healers (Flueckiger 2006). In Indonesia women college students have taken on more modest forms of veiling as a strategy to more comfortably navigate new educational opportunities and fields of study traditionally dominated by men (Smith‐Hefner 2007).…”
Section: Friends Who Keep You On the Pious Pathmentioning
confidence: 99%
“…These phenomena speak to broader themes in the anthropology of Islam, gender, and religious authority, in which ethnographic studies have demonstrated how women take up the mantle of Muslim femininity to maintain their respectability as they claim territory in social and authoritative roles and spaces once the purview of men. Women may extol the virtues of Muslim gender norms while simultaneously claiming new forms of religious authority as women preachers (Kalmbach 2008; Kloos 2021), activists (Deeb 2006), Sufi teachers within a patrilineal lineage (Hill 2018), or healers (Flueckiger 2006). In Indonesia women college students have taken on more modest forms of veiling as a strategy to more comfortably navigate new educational opportunities and fields of study traditionally dominated by men (Smith‐Hefner 2007).…”
Section: Friends Who Keep You On the Pious Pathmentioning
confidence: 99%
“…This need not happen if we all understand what we should do, what our rights are, and what our obligations are in relation to the inheritance. Ignorance and lack of understanding are the cause of many of these conflicts (Kloos, 2021). The question that arises every time someone dies, is "How should the inheritance (if any) be distributed to those entitled to receive it and to whom the property is transferred, and how.…”
Section: Introductionmentioning
confidence: 99%
“…Second, studies focus on discussing the trend of da'wah among urban millennial Muslims in the context of adaptation (Friberg & Sterri, 2021;Mihlar, 2019;Bennigsen, 2019). Third, studies focus on discussing the trend of da'wah among urban millennial Muslims in the context of practice (Thaib, 2020;Kloos, 2021;Rijal, 2020). The three contexts show that the trend for the emergence of new religious authority among urban millennial Muslims does not only arise naturally but is influenced by various factors (Wati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%